Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Pegawai Melalui Kualitas Pelayanan Sebagai Variabel Intervening Pada Badan Pendapatan Daerah (Bapenda) Kota Palembang - Nadya Afifah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of organizational culture, communication, and service quality on employee performance at the Regional Revenue Agency (Bapenda) of Palembang City. The research method used is quantitative with a descriptive correlational approach, utilizing a survey with questionnaires. The research sample consisted of 80 employees from Bapenda Palembang. The results indicate that organizational culture and communication have a significant influence on service quality and employee performance. Service quality was also found to have a positive impact on employee performance. Additionally, there is an indirect influence of organizational culture and communication on employee performance through service quality as an intervening variable. This study provides insights into the importance of strengthening organizational culture and communication in improving service quality and employee performance at Bapenda Palembang City.